Fungi and Fungal Metabolites for the Improvement of Human and Animal Nutrition and Health - Dufossé, Laurent; Fouillaud, Mireille; Caro, Yanis (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The purpose of this book was not to provide a comprehensive overview of the vast arena of how fungi and fungal metabolites are able to improve human and animal nutrition and health; rather, we, as Guest Editors, wished to encourage authors working in this field to publish their most recent work in this rapidly growing journal in order for the large readership to appreciate the full potential of wonderful and beneficial fungi. Thus, this Special Issue welcomed scientific contributions on applications of fungi and fungal metabolites, such as bioactive fatty acids, pigments, polysaccharides, alkaloids, terpenoids, etc., with great potential in human and animal nutrition and health.